Insights into Novel Supramolecular Complexes of Two Solid Forms of Norfloxacin and β‐Cyclodextrin. Issue 10 (31st July 2013) - Chattah, Ana K.; Mroue, Kamal H.; Pfund, Laura Y.; Ramamoorthy, Ayyalusamy; Longhi, Marcela R.; Garnero, Claudia
<x xml:space="preserve">Abstract</x> The solid‐state properties of novel complexes of β‐cyclodextrin and two different solid forms of norfloxacin were investigated at the molecular level, in an attempt to obtain promising candidates for the preparation of alternative matrices used in pharmaceutical oral formulations. In order to evaluate the physical properties inherited from the different polymorphs, these supramolecular systems were characterized using a variety of spectroscopic techniques including natural‐abundance 13C cross‐polarization magic‐angle‐spinning (CP‐MAS) nuclear magnetic resonance (NMR), powder X‐ray diffraction, and Fourier transform infrared spectroscopy. The intrinsic proton spin‐lattice relaxation times detected in 13C CP‐MAS NMR spectra are used to confirm and distinguish the complex formation, as well as to provide better insights into the molecular fragments that are involved in the interaction with β‐cyclodextrin. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3717–3724, 2013